A inclus\~ao produtiva como eixo de política de proteç\~ao social: Contexto latino-americano e quest\~oes para a realidade brasileira - Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This text aimed to provide an analytical framework about the recent repertoire of public policies to combat poverty and income inequality, its most central characteristics and how productive inclusion programs are part of this strategy. To this end, an overview was drawn up that characterizes this institutional arrangement in the current Latin American context. Then, the focus was on recent experiences in Brazil, highlighting the main programs that fall within a social protection strategy in general, and productive inclusion in particular. To complement the discussion, a bibliometric research was carried out on the basis of scientific production that addresses the theme 'productive inclusion', in order to ascertain the diversity of interpretations that the term elicits. Finally, in the final considerations, some general propositional guidelines are pointed out for the construction of a national strategy for productive inclusion in Brazil.
Keywords: I31; J68; 330; productive inclusion; social policy; work and income